4-hydroxynonenal, an endogenous aldehyde, causes pain and neurogenic inflammation through activation of the irritant receptor TRPA1 - Trevisani, Marcello; Siemens, Jan; Materazzi, Serena; Bautista, Diana M.; Nassini, Romina; Campi, Barbara; Imamachi, Noritaka; Andrè, Eunice; Patacchini, Riccardo; Cottrell, Graeme S.; Gatti, Raffaele; Basbaum, Allan I.; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2007)
TRPA1 is an excitatory ion channel expressed by a subpopulation of primary afferent somatosensory neurons that contain substance P and calcitonin gene-related peptide. Environmental irritants such as mustard oil, allicin, and acrolein activate TRPA1, causing acute pain, neuropeptide release, and neurogenic inflammation. Genetic studies indicate that TRPA1 is also activated downstream of one or more proalgesic agents that stimulate phospholipase C signaling pathways, thereby implicating this channel in peripheral mechanisms controlling pain hypersensitivity. However, it is not known whether tissue injury also produces endogenous proalgesic factors that activate TRPA1 directly to augment inflammatory pain. Here, we report that recombinant or native TRPA1 channels are activated by 4-hydroxy-2-nonenal (HNE), an endogenous α,β-unsaturated aldehyde that is produced when reactive oxygen species peroxidate membrane phospholipids in response to tissue injury, inflammation, and oxidative stress. HNE provokes release of substance P and calcitonin gene-related peptide from central (spinal cord) and peripheral (esophagus) nerve endings, resulting in neurogenic plasma protein extravasation in peripheral tissues. Moreover, injection of HNE into the rodent hind paw elicits pain-related behaviors that are inhibited by TRPA1 antagonists and absent in animals lacking functional TRPA1 channels. These findings demonstrate that HNE activates TRPA1 on nociceptive neurons to promote acute pain, neuropeptide release, and neurogenic inflammation. Our results also provide a mechanism-based rationale for developing novel analgesic or anti-inflammatory agents that target HNE production or TRPA1 activation.
Gesehen am 06.12.2021